Problems associated with reconstruction of the Bashkir folk costume based on ethnographic photographs of the mid-19th–early 20th centuries - S.M. Usmanova (Ученые записки Казанского университета: Серия Гуманитарные науки, 2022)
This article discusses how ethnographic photographs are used for reconstructing the Bashkir national costume and its details. The results obtained show that the historical reconstruction of the Bashkir national costume has developed and advanced through various competitions between folk clothing artists in the Republic of Bashkortostan. The photographs, published both in various print sources and online, of the collections from the museums of St. Petersburg, Moscow, and Ufa, have inspired their reconstructions. Many costume pieces have been reconstructed based on the photographs taken during the 19th–20th centuries by travelers, scholars, and individual persons. Interestingly, the engravings of the 18th century and the written sources have not been used. Some ethnoterritorial variants of the Bashkir costume (southern, northeastern, Demsky, and northwestern) and those of certain age groups (clothes typically worn by girls and boys) have been restored. So far, there have been no reconstructions of the costumes of elderly men and women, city nobility, as well as the clothing traditions of the Bashkir groups in Samara, Sverdlovsk, and Orenburg. It was concluded that historical reconstruction of the folk costume contributes significantly to a better understanding of the ethnic features of the clothing culture.